A Study on the Application of PBL Teaching Method in the Course of Principles of Education under the Background of Multiple Majors - Zhang, Baolin (Journal of Educational Research and Policies, 2025)
This paper focuses on the application of PBL teaching method in the course of “Principles of Education” in the context of multiple majors. The beginning details the evolution of research on educational principles in my country, as well as the key position and significance of this course in the pedagogy discipline system. Then, the PBL teaching method is interpreted in depth, its core connotation of problem-oriented and student-centered is explained, and the necessity of applying it to the “Principles of Education” course is analyzed. This article focuses on the practical application of PBL teaching method in the teaching of “Principles of Education” course, and deeply explores the application value of PBL teaching method in this course. The research results show that the PBL teaching method is highly consistent with the requirements of the “Principles of Education” course, which can significantly improve students’ understanding of educational theory, enhance students’ ability to apply theory to practice, and provide strong support for improving the quality of education and teaching.